Think Locally, Act Globally: Reflections on Virtual Neighbourhoods - Elkins, David J. (Javnost-The Public, 1999)
The article proposes to explore extrapolations of ideas previously applied to ethnic groups in light of advancements in telecommunication technologies. It briefly examines several related topics including the transformation of identities in diasporas, the shifting boundaries between public and private realms, how certain kinds of diversity may be sustained in the face of cultural imperialism, and some issues in policing the Internet of WWW. It explores the idea that the introduction of new technologies may enable the creation and maintenance of “virtual neighbourhoods,” which retain the sense of affinity among neighbours found in traditional small-scale, focused geographical neighbourhoods. This point emphasises the fact that affinity is based on focused interest rather than proximity. Telecommunication technologies used in the ways hypothesised here have effectively redefined the word “local” so that it now encompasses two senses; geographically focused (proximate) and focused (shared) interest. The resulting conclusion asserts that variations in exposure to media, entertainment, foreign languages, and cultural forces generally will occur within territorial states as much as between them, thereby to a certain extent supplanting proximate, geographical neighbourhoods with remarkably different virtual neighbourhoods. The voluntaristic nature of virtual neighbourhoods based on shared interests means that they will likely not become “virtual ghettos”.